报告 国际麻醉品管制局 2013 年 - United Nations (United Nations, 2014)
The report contains an analysis of the drug control situation worldwide so that Governments are kept aware of existing and potential situations that may endanger the objectives of the international drug control treaties. Divided into four parts, it covers the following topics: drugs and corruption, functioning of the international drug control system, analysis of the world situation and finally, a set of recommendations to Governments, the United Nations and other relevant international and regional organizations. A set of Annexes follows as well.